Penerapan Restorative Justice Dalam Sistem Peradilan Pidana Anak - Jaka Prima (JOSH: Journal of Sharia, 2024)
The application of restorative justice with certain requirements must be implemented and used to provide opportunities and possibilities for crime victims to obtain restitution, a sense of security, enable perpetrators to understand the causes and consequences of their behavior and take responsibility in a meaningful way and enable society to understand the main causes of crimes, to promote society's sense of justice and prevent crime. A special restorative justice process strategy for children/adolescents that is balanced should be based on the idea that the source of children's crimes and violations is the community, family, school, so that strategies that only focus on individual perpetrators are not appropriate. This restorative justice will feature flexible procedures and a series of actions that can be adapted to the applicable criminal justice system and are fair to the parties.